A Structural Equation Modeling Analysis of Influences on Juvenile Delinquency. (May 2014) - Barrett, David E.; Katsiyannis, Antonis; Zhang, Dalun; Zhang, Dake
This study examined influences on delinquency and recidivism using structural equation modeling. The sample comprised 199, 204 individuals: 99, 602 youth whose cases had been processed by the South Carolina Department of Juvenile Justice and a matched control group of 99, 602 youth without juvenile records. Structural equation modeling for the outcome of delinquent versus nondelinquent status showed direct paths of two latent constructs, developmental exceptionalities and early parenting problems, to delinquent outcome, with developmental problems also mediating the relationship between adverse parenting and delinquency. Separate analysis of the delinquent group indicated gender differences in the predictors of more serious offending (early arrests and recidivism), with adverse parenting a significant influence for girls only. Implications for prevention of juvenile delinquency were addressed.